2015
DOI: 10.1177/1744629515615267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical needs and outcomes of adults with intellectual disabilities accessing an inpatient assessment and treatment service and the implication for development of community services

Abstract: The role and future of assessment and treatment units for people with intellectual disabilities is once again the focus of debate and government policy. Reviewing the admissions to inpatient services can provide useful information about the characteristics, needs and clinical outcomes of clients. Data were collected retrospectively for all 36 referrals accepted to an inpatient assessment and treatment unit for people with intellectual disability, between January 2013 and April 2014. Clinical and demographic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Research has suggested that demographics such as poorer levels of functioning, rates of self‐harming and challenging behaviour are more prevalent in adults who are admitted to inpatient units than those managed within local community services (Pearce et al, 2011). This has correlated in adults with higher HoNOS‐LD scores being admitted compared to adults commencing community‐based psychiatric/behavioural intervention (Pearce et al, 2011; Sandhu & Tomlins, 2017). Future research could assess if community services are as effective as inpatient units in improving clinical outcomes of the demographic of patients, who often have higher baseline HoNOS‐LD scores, that are often referred to inpatient services.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that demographics such as poorer levels of functioning, rates of self‐harming and challenging behaviour are more prevalent in adults who are admitted to inpatient units than those managed within local community services (Pearce et al, 2011). This has correlated in adults with higher HoNOS‐LD scores being admitted compared to adults commencing community‐based psychiatric/behavioural intervention (Pearce et al, 2011; Sandhu & Tomlins, 2017). Future research could assess if community services are as effective as inpatient units in improving clinical outcomes of the demographic of patients, who often have higher baseline HoNOS‐LD scores, that are often referred to inpatient services.…”
Section: Discussionmentioning
confidence: 99%
“…Nine papers focused on measures of patient safety with adults with intellectual disabilities and/or autism. 52,56,71,73,74,78,104,112,117 Eligible papers for outcome domain synthesis = 103 Fig. 2 A frequency count of the number of studies categorised according to one of three outcome domains: measures of effectiveness, measures of patient safety or measures of patient experience.…”
Section: Measures Of Patient Safetymentioning
confidence: 99%
“…2,5 Within studies, GMH and specialist intellectual disability inpatient services were described using different language, such as acute assessment and treatment, 76 or services for 'longer-stay' patients. 77 Some authors described the purpose for admission and the expected duration of stay, such as admission for assessment and treatment, 78 or emergency care/admission with short stays. 26 Details of 'aftercare' following discharge, including collaborative working with community services, were absent from much of adult literature.…”
Section: Models Of Service Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…After analysis of the existing evidence, we hypothesised that that lower intellectual functioning is associated with more severe illness, a poorer prognosis and worse functioning. We know from several intellectual disability studies 25 , 26 in patients with MID in the UK, the USA and Finland, that schizophrenia, psychotic disorders, aggression and alcohol and substance misuse are often reasons for hospital admission and long-term treatment. Looking at the distribution of diagnoses in the patients with an SCIL score of ≤19, schizophrenia (odds ratio 2.41), substance use disorder (odds ratio 1.84) and intellectual disability (odds ratio 7.11) are significantly more often diagnosed than in patients with an SCIL score of ≥20.…”
Section: Discussionmentioning
confidence: 99%